YAP1 activates SLC2A1 transcription and augments the malignant behavior of colorectal cancer cells by activating the Wnt/β-catenin signaling pathway - Kunpeng Li; Ya-Jie Dai; Haifeng Zhang; Zhigang Zhang (Cell Division)
Abstract Objective This paper examined the role of solute carrier family 2 member 1 (SLC2A1) in colorectal cancer (CRC) progression, focusing on its expression levels, functional implications, and regulatory mechanisms involving Yes-associated protein 1 (YAP1) and the Wnt signaling pathway. Methods GEO datasets (GSE14297, GSE18462, GSE40367) were analyzed to identify genes linked to metastasis in CRC, and TCGA-COAD system was used to analyze the expression pattern and prognostic values of SLC2A1 in CRC. Functional studies were conducted using CRC cell lines (Caco-2 and SW480). Cell viability, migration and invasion, and apoptosis were examined using EdU assays, Transwell assays, and flow cytometry. YAP1’s regulatory role on SLC2A1 was investigated using ChIP-qPCR and luciferase reporter assays. The Wnt/β-catenin agonist SKL2001 was used for functional rescue experiments. Results SLC2A1 was upregulated in CRC cells, and its upregulation was associated with tumor metastasis and unfavorable outcomes according to bioinformatics. Knockdown of SLC2A1 resulted in reduced cell viability, decreased migration, and increased apoptosis in Caco-2 and SW480 cells. Additionally, YAP1 was identified as a transcriptional activator of SLC2A1. Knockdown of YAP1 decreased SLC2A1 expression and reduced expression of Wnt target genes, thus suppressing malignant behavior of tumor cells. However, further overexpression of SLC2A1 restored cell viability and migration in YAP1-deficient cells. The YAP1- SLC2A1 axis activated the Wnt/β-catenin by reducing GSK3β activity. Conclusion SLC2A1 is critical in CRC progression, with YAP1 serving as a key regulator of its expression and function. The YAP1-SLC2A1-Wnt axis represents a potential therapeutic target for CRC, providing insights into metabolic adaptations that support tumor growth and metastasis.